2006
DOI: 10.1186/1471-2156-7-48
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping faecal samples of Bengal tiger Panthera tigris tigris for population estimation: A pilot study

Abstract: Background: Bengal tiger Panthera tigris tigris the National Animal of India, is an endangered species. Estimating populations for such species is the main objective for designing conservation measures and for evaluating those that are already in place. Due to the tiger's cryptic and secretive behaviour, it is not possible to enumerate and monitor its populations through direct observations; instead indirect methods have always been used for studying tigers in the wild. DNA methods based on non-invasive sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
97
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(102 citation statements)
references
References 48 publications
(55 reference statements)
4
97
0
Order By: Relevance
“…The technique involves the extraction of DNA from materials like faeces, shed hair, feathers, urine and sloughed skin (Höss et al 1992; Kohn and Wayne 1997;Goossens et al 1998;Segelbacher 2002;Fernando et al 2003). The methodology has been increasingly applied to a wide variety of species (Taberlet et al 1997;Reed et al 1997;Kohn et al 1999;Ernest et al 2000;Garnier et al 2001;Eggert et al 2003;Goossens et al 2003;Hedmark et al 2004;Vidya and Sukumar 2005;Smith et al 2006;Bhagavatula and Singh 2006). Studies on the genetic diversity of tigers have focused on mitochondrial DNA (Zhang et al 2006a), and microsatellites (Zhang et al 2006b;Xu et al 2005;Williamson et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique involves the extraction of DNA from materials like faeces, shed hair, feathers, urine and sloughed skin (Höss et al 1992; Kohn and Wayne 1997;Goossens et al 1998;Segelbacher 2002;Fernando et al 2003). The methodology has been increasingly applied to a wide variety of species (Taberlet et al 1997;Reed et al 1997;Kohn et al 1999;Ernest et al 2000;Garnier et al 2001;Eggert et al 2003;Goossens et al 2003;Hedmark et al 2004;Vidya and Sukumar 2005;Smith et al 2006;Bhagavatula and Singh 2006). Studies on the genetic diversity of tigers have focused on mitochondrial DNA (Zhang et al 2006a), and microsatellites (Zhang et al 2006b;Xu et al 2005;Williamson et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…By employing both mitochondrial and nuclear genetic markers, DNA isolated from tissue sources have been used to update and delineate the taxonomic status among the five living tiger subspecies (Luo et al 2004). Studies have demonstrated the feasibility of using the noninvasive genetic technique for counting tiger individuals through genetic identification of individuals from field collected faecal samples of wild tigers in India (Bhagavatula and Singh 2006) and for species identification (Mukherjee et al 2007) and sex identification (Sugimoto et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Microsatellite amplification and analysis of tiger positive scat samples Tiger positive samples were analyzed with primers targeting 10 tetranucleotide loci (Menotti-Raymond et al 1999) and four dinucleotide loci (Bhagavatula and Singh 2006;Menotti-Raymond et al 1999;Williamson et al 2002) by a two-step multiplex PCR assay (Arandjelovic et al 2009). In the initial step, all microsatellite loci were amplified in a single reaction in 50-μl reaction volumes consisting of 1× PCR buffer II (Applied Biosystems), 2.5 mM MgCl 2 (Applied Biosystems), 15 pmol of each primer (unlabeled), 200 μM dNTPs, 1× BSA (New England Biolabs), 2.5 U of AmpliTaq Gold (Applied Biosystems), and 5 μl of template DNA.…”
Section: Gis Data and Sample Collectionmentioning
confidence: 99%
“…All isolation sets of 10 samples each, included a control to monitor for contamination. A PCR assay with tiger-specific cytochrome b primers (TIF and TIR) developed to identify tiger scats from those of sympatric carnivores, like leopards, was used to screen all the scat samples (Bhagavatula and Singh 2006). All the PCR products were electrophoresed and only the tiger positive samples were subjected to further analysis.…”
Section: Gis Data and Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation